Biochemical and physiological effects of propagule type and auxin concentration on adventitious root formation in novel Jasmine genotypes - Keerthivasan R; Ganga M; Chitra R; Vanitha K; Sharmila Rahale C (Plant Science Today, 2024)
Jasmine is primarily propagated through asexual methods, and bio-stimulants can improve soil fertility around plant roots. Some jasmine genotypes are mainly propagated through cuttings; however, the rooting process is slow and inconsistent. Specific jasmine genotypes are primarily propagated through cuttings, but the rooting process is slow and uneven. This study evaluated the regeneration potential of stem cuttings by investigating the effects of auxins and various propagule types on adventitious root formation, along with associated biochemical changes. A field experiment conducted by the Department of Floriculture and Landscaping at TNAU, Coimbatore, Tamil Nadu, from December 2023 to June 2024, during the winter monsoon, investigated the rooting of stem cuttings in three Jasminum genotypes using auxin. Stem cuttings of J. sambac Double Flower type (DF), J. grandiflorum White Flower type (WF) and a new cultivar of J. multiflorum CO.1 Winter Jasmine (CO.1 WJ) were treated with three Indole-3-Butyric Acid (IBA) concentrations (0.5, 1, 1.5 g L-1) and distilled water as control. Utilizing a Factorial, Completely Randomized Design for terminal and semi-hardwood cuttings, the study found that rooting hormone significantly enhanced root formation and stem and shoot growth. Semi-hardwood cuttings of J. sambac (DF) treated with 1g L-1 IBA had the highest rooting rate (88.60%), number of roots (9.34), root length (12.74 cm), shoot length (10.26 cm) and number of leaves (6.60). The highest rooting rate of 48.15% was obtained from the terminal cuttings of J. grandiflorum (WF) that had been treated with 1g L-1 IBA, in addition to other parameters such as number of roots (13.52), root length (12.03 cm), shoot length (14.30 cm), and number of leaves (13.48). On the other hand, J. multiflorum (CO.1 WJ) recorded the highest rooting rate of 72.23%, root number of 16.52, root length of 17.22 cm, shoot length of 14.14 cm and number of leaves, which was pegged at 31.70 when terminal cuttings were treated with 1g L-1 IBA. The current findings indicate that the application of auxins is crucial for promoting early root initiation and achieving higher rooting success, making it advantageous for vegetative propagation.